Effect of Crack Propagation on Condition Assessment of Aged Offshore Jacket Platform - Murthy, Kiren Raj (Universiti Teknologi PETRONAS, 2017)
The project will focus on how fatigue crack could influence the overall stability and performance of a jacket platform. Offshore structures are vital for continuous hydrocarbon exploration. Fatigue and crack growth on the structural members of jacket structures have been recognized to be one of the most predominant factors that determines the strength of platform. Hence, fatigue hazards require detail assessment to avoid jacket platform from unfortunate failure. An advanced approach using software simulation is presented in this study to determine whether fatigue crack growth influences the stability and performance of the jacket platform. ANSYS Workbench is used to model crack propagation at K-joint of the jacket structure. Paris Law method is integrated to determine the crack sizes that will occur at the joints. The crack data to be integrated into SACS software. Pushover analysis to be simulated to study the Reserve Strength Ratio (RSR) of the platform which eventually will demonstrate the effect of cracks to the stability of the structure.